Pigou meets mirrlees: On the irrelevance of tax distortions for the second-best Pigouvian tax - Bas Jacobs; Ruud A. de Mooij (Center for Economic Studies and ifo Institute (CESifo), 2011)
This paper extends the Mirrlees (1971) model of optimal income redistribution with optimal corrective taxes to internalize consumption externalities. It is demonstrated that the optimal second-best tax on an externality-generating good should not be corrected for the marginal cost of public funds. The reason is that the marginal cost of public funds equals unity in the optimal tax system, since marginal distortions of taxation are equal to marginal distributional gains. The Pigouvian tax needs to be modified, however, if polluting commodities or environmental quality are more complementary to leisure than non-polluting commodities are.
Keywords: D62; H21; H23; 330; marginal cost of public funds; optimal environmental taxation; optimal redistribution; externalities; Optimale Verteilung; Internalisierung externer Effekte; Second Best; Ökosteuer; Optimale Besteuerung; Theorie